Dimensions of Place in Imru’ Al-Qays’s Poetry - Sara Falah Mohammed (QALAAI ZANIST JOURNAL, 2022)
This research seeks to reveal the social and psychological dimensions of place in the poetry of Imru’ Al-Qays. This involves the importance of the place for the poet, how he addresses it, his standing on the ruins and remains of home, his crying and addressing his friend, and asking the house and the place about the location of the loved ones with the hope of receiving an answer about their whereabouts after they abandoned him and were absent from the place of their meeting. The beloved has departed, and the memories that are not absent from the poet’s heart remained immortal in his mind. The research starts with an introduction and then a preface that explains the importance of the place for poets in general and for Imru’ Al-Qays in particular. This is followed by studying the dimensions indicated by the place in the poetry of Imru’ al-Qays, such as the social and psychological dimensions, and their manifestations in his poetry, in addition to shedding light on the poems that he cited in his expression of the place and the vocabulary that refers to it.